Isolated Langerhans Cell Histiocytosis of the Vulva in a 28-Year-Old Lady: A Report of a Case and Brief Review of the Literature. (28th June 2022) - Sadati, Maryam Sadat; Todarbary, Nafiseh; Sari Aslani, Fatemeh; Hadibarhaghtalab, Maryam
Abstract : Langerhans cell histiocytosis (LCH) is a rare, proliferative disorder of Langerhans' cells. The presentation can vary from single organ involvement to multisystem and disseminated in severe cases, affecting children more than adults. Isolated vulvar involvement of LCH in a 28-year-old woman has rarely been described and also there are limited data for diagnosis and treatment. Herein, we report the case of a 28-year-old woman with isolated vulvar LCH, misdiagnosed with herpes simplex infection, successfully treated with thalidomide.